Wall conditioning by ECRH discharges and He-GDC in the limiter phase of Wendelstein 7-X. (20th April 2018) - Wauters, T.; Brakel, R.; Brezinsek, S.; Dinklage, A.; Goriaev, A.; Laqua, H.P.; Marsen, S.; Moseev, D.; Stange, T.; Schlisio, G.; Pedersen, T. Sunn; Volzke, O.; et al.
Abstract: Wendelstein 7-X (W7-X) relies on wall conditioning to control the density and the impurity content of the plasma. Wall conditioning in the first operation campaign of W7-X consisted of baking at 150 °C during 1 week prior to operation, glow discharge conditioning (GDC) in helium (He) and electron cyclotron resonance heating (ECRH) discharges. Additionally, the usage of He-GDC was limited to avoid sputtering and migration of metallic plasma facing components. This presented a unique opportunity for studying the applicability of ECRH discharges for initial wall conditioning on a stellarator, albeit in the carbon limiter configuration. A single envelope curve is observed in the normalised outgassing data that takes into account all ECRH discharges. This illustrates that the majority of discharges operates at the limits of a radiative collapse. Hydrogen recycling dominated the fuelling of ECRH discharges throughout while CO outgassing was found strongest at the start of the campaign. A reduction of recycling was observed throughout the campaign. Temporarily depleting the walls from H and impurities was possible by He-GDC. It was shown that the recycling coefficient in -ECRH plasmas could be reduced and the pulse duration significantly extended by He-'recovery' ECRH plasmas. Good wall conditions were defined by normalised outgassing values below mbar kJ −1 . In absence of -GDC, more than 311 cumulated discharge seconds of ECRH discharges are needed for obtaining lasting low outgassing levels. A release model with two trapping reservoirs could reproduce the normalised outgassing trend, including ECRH and GDC plasma wall interactions.